Enhancing high-intensity actions during a basketball game after a strength training program with random recovery times between sets - Arede, J.; Leite, N.; Tous-Fajardo, J.; Bishop, C.; Gonzalo-Skok, O. (The Journal of Strength and Conditioning Research, 2022)
To examine the effects of a strength training program with random recovery times between sets in consideration of several physical parameters, high-intensity actions, and spatial exploration index during a simulated basketball game. Twenty male basketball players (age: 19.45 ± 4.36 years) were assigned randomly to either strength training group (n = 10) or control group (n = 10). The strength training included parallel back squat and bench press exercises, twice a week for the duration of 10 weeks, with 2 blocks of 5 sets × 5 repetitions interspersed with variable passive recovery (range = 15-35 seconds) between sets, and constant passive recovery (3 minutes) between blocks with the load that maximized propulsive power output. The pre- and posttest assessments included jumping (bilateral and unilateral), change of direction, straight sprinting, and a 5-on-5 full-court situation. The external training load was assessed using the local positioning system, and the internal load was recorded with the use of individual heart rate monitors. A significant interaction effect (group × time) was observed on countermovement jump, unilateral right hops, high-intensity accelerations and decelerations, and peak accelerations and decelerations in the 5-on-5 full-court situation. Relative improvements observed and recorded in the training group on unilateral right hops, accelerations, and decelerations were correlated. Similar results were observed on 0- to 25-m sprints, high-intensity decelerations, peak accelerations, and decelerations. Strength training paired with random recovery times enhanced physical and game-related aspects in the observed basketball players.